(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
In recent years, the role of tax incentives and preferences has been increasing. In the conditions of the ongoing post-crisis period, many states actively apply preferential taxation as one of the main mechanisms for regulating economic relations. This tool allows you to stimulate or restrain the pace of reproduction of certain types of products, strengthen or weaken capital accumulation, expand or reduce the effective demand of the population. The provision of benefits and preferences is aimed at attracting investments in modernization and diversification, both basic and strategically important sectors of the economy, the creation of necessary infrastructure facilities.